Tapping International Equity Markets Through Depository Receipts : Lessons from the Telecoms Sector - Mustafa, Mohammad A. (World Bank, Washington, DC, 2012)
Ongoing privatization and financial liberalization in emerging economies have let to continuous growth in the number of depository receipt offerings from these countries. Asian and Latin American companies have been the biggest source of offerings. The main advantages of depository receipts stem from the greater market depth and liquidity offered by international capital markets: telecommunications companies are sometimes too big for local markets to absorb, and more active trading attracts a wider shareholder base, implies continuous evaluation of a company's value, and increases management's accountability for a company's financial performance. International offerings also enhance the legitimacy of shares because companies must comply with transparent accounting rules and strict disclosure standards in the host market. Experience has shown that to guard against failure of a depository receipt issue, much effort needs to be put into choosing the right type of depository receipts, marketing the issue, forecasting investor demand, and determining the share price.